Long-Duration Oral Vancomycin to Treat Clostridioides difficile in Patients With Inflammatory Bowel Disease Is Associated With a Low Rate of Recurrence. (December 2019) - Lei, Donald K.; Ollech, Jacob E.; Andersen, Michael; Weisshof, Roni; Zmeter, Nada; Sossenheimer, Philip; Rubin, David T.
Abstract : OBJECTIVES: Patients with inflammatory bowel disease (IBD) are susceptible to Clostridioides difficile infections (CDIs), suffering from greater morbidity and mortality than the general population. Previous studies have proven the efficacy of oral vancomycin therapy in CDI, but there are no definitive guidelines to treat patients with IBD. We assessed the relationship between the length of vancomycin therapy and rates of CDI recurrence and reinfection in patients with IBD. METHODS: We compared rates of CDI recurrence and reinfection in Crohn's disease and ulcerative colitis (UC) patients receiving long-duration (LD) and short-duration (SD) oral vancomycin therapy, defined as 21–42 days and 10–14 days, respectively. Recurrence and reinfection were defined as positive C. difficile toxin assay by polymerase chain reaction within 8 weeks of the end of antibiotic therapy and after 8 weeks of the end of antibiotic therapy, respectively. The Fisher exact test was used to test for significance, and multivariate logistic regression models were constructed to control for other covariables. RESULTS: One hundred thirty-four patients with IBD (57 ulcerative colitis and 77 Crohn's disease) met inclusion criteria. LD vancomycin had a 1.8% incidence of CDI recurrence, compared with 11.7% in the SD vancomycin group (odds ratio = 0.13, P = 0.043). CDI reinfection rates and time to reinfection were not significantly different (LD 14.0% vs SD 16.9%, P = NS). Multivariate logistic regression models showed that treatment with LD vancomycin had lower odds for recurrence than SD vancomycin (odds ratio = 0.03, P = 0.021). DISCUSSION: LD vancomycin is associated with lower rates of CDI recurrence compared with SD vancomycin therapy. These results will help guide clinical decisions and the development of a prospective trial.